Assessing the adoption of high-iron bean varieties and their impact on iron intakes and other livelihood outcomes in Rwanda: Main survey report - Asare-Marfo, Dorene; Herrington, Caitlin; Birachi, Eliud; Birol, Ekin; Cook, Kristy; Diressie, Michael Tedla; Dusenge, Leonidas; Funes, José; Katsvairo, Lister; Katungi, Enid; Labarta, Ricardo; LaRochelle, Catherine; et al. (International Food Policy Research Institute, 2017)
An impact assessment (IA) study was conducted in Season B 20152 to establish the reach of high-iron bean (HIB) varieties to Rwandan bean farmers since these varieties were released in 2010, and to understand the adoption and diffusion patterns that have occurred so far. The IA was carried out in two parts. The first part was a listing survey, which was conducted at the beginning of Season B 2015, during the planting period. A total of 19,575 households were enlisted in 120 randomly selected villages throughout the country, and 93 percent of those households were bean-producing households. The listing exercise revealed that 28 percent of bean farmers had grown at least one HIB variety in at least one season, since 2010—the equivalent of approximately half a million households. In Season B 2015, 20 percent of bean farmers were reported to be growing an HIB—the equivalent of approximately 350,000 households. Detailed results of the listing exercise are available in a separate report3. The second part of the study was a more detailed household survey, which was conducted among a subsample of nearly 1,400 bean-farming households, immediately after harvest had taken place. Both the listing and main household survey are nationally representative of rural bean producing households in Rwanda. This report presents key descriptive results from the main survey and sheds light on issues that may be investigated further in forthcoming publications. Key takeaways from the report are summarized below.